Föräldraalienation i vårdnadsmål. En rättssociologisk studie om hur domstolar skapar legitimitet för sina beslut - Lavinen,Estee (2023)
The purpose of the thesis is to describe and analyze, from a socio-legal perspective, how appellate courts create legitimacy for their decisions in custody cases concerning custody, residence, and visitation where the phenomenon of parental alienation occurs. Parental alienation is when a child is deliberately turned against one of their parents through manipulation or influence, often by the other parent, resulting in a strained or broken relationship between the child and the targeted parent. The method of the thesis consists of qualitative content analyses of appellate court cases where some form of parental alienation has occurred, negatively influencing the child's attitude towards the other parent, and excludes cases where the reason the child has no contact with one of their parents is that the visitation would pose a danger to the child. The empirical evidence reveals the interplay and occasional conflicts between norms and values in the court's decision-making process, forming a normative structure. The court must consider both parental responsibilities and the child's need for contact with both parents. Balancing the principle of continuity and the child's right to contact can be challenging, with no clear prioritization rule. However, when the principle of contact conflicts with the safety of the custodial parent, the latter is given greater weight. There is also a conflict between considering the child's wishes and ensuring their best interests as the primary factor in custody disputes. Taking the child's perspective into account is crucial to guarantee their rights, but their expressed desires may conflict with their best interests, especially in cases of parental alienation. The analysis confirms the lack of transparency in assessing the child's best interests and wishes in court decisions, as highlighted by Ryrstedt in 1999. While the overarching principle of the child's best interests permeates court reasoning, its concrete evaluation and valuation in different cases remain unclear. Additionally, the child's right to be informed and express their opinions is not extensively discussed in the court decisions.
Keywords: parental alienation; child custody; access sabotage; appellate court; best interest of the child